2004
DOI: 10.1074/jbc.m405867200
|View full text |Cite
|
Sign up to set email alerts
|

The Family 11 Carbohydrate-binding Module of Clostridium thermocellum Lic26A-Cel5E Accommodates β-1,4- and β-1,3–1,4-Mixed Linked Glucans at a Single Binding Site

Abstract: Modular glycoside hydrolases that attack recalcitrant polymers generally contain noncatalytic carbohydratebinding modules (CBMs), which play a critical role in the action of these enzymes by localizing the appended catalytic domains onto the surface of insoluble polysaccharide substrates. Type B CBMs, which recognize single polysaccharide chains, display ligand specificities that are consistent with the substrates hydrolyzed by the associated catalytic domains. In enzymes that contain multiple catalytic domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
71
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 39 publications
10
71
0
2
Order By: Relevance
“…Surface recognition by proteins has also been observed in biopolymers in biological systems (1,2). Furthermore, the use of recent combinatorial library approaches has enabled the identification of short peptides with affinity for nonbiological inorganic materials (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface recognition by proteins has also been observed in biopolymers in biological systems (1,2). Furthermore, the use of recent combinatorial library approaches has enabled the identification of short peptides with affinity for nonbiological inorganic materials (3)(4)(5).…”
mentioning
confidence: 99%
“…S1. 1 To whom correspondence may be addressed: Aoba 6-6-11-608; Aoba-ku, Sendai 980-8579, Japan. chain camel antibody (VHH) to give a VHH fragment with the same affinity as the grafted peptide and without structural instability.…”
mentioning
confidence: 99%
“…A bifunctional cellulase from Clostridium thermocellum was shown to contain an N-terminal family 26 glycoside hydrolase called lichenase (Lic26A) [2] and an internal family 5 glycoside hydrolase (GH5) [3] catalytic domains and a C-terminal family 11 carbohydrate-binding module (CBM11) [4,5]. It was demonstrated that the carbohydratebinding module (CBM11) of bifunctional cellulase binds to ligands that are substrates for both Lic26A and GH5 catalytic modules [4]. The crystal structure of lichenase has been determined and interestingly it has been shown that the enzyme displays high activity towards lichenan and the mechanism of binding and catalysis of lichenan was proposed [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulosome functions as a comprehensive enzymatic system that includes cellulases, hemicellulases, and others to synergistically break heterogeneous polysaccharides; it thus has a huge potential in biofuel application. Previous studies of C. thermocellum revealed an interesting cellulosomal celH gene that encodes two functional enzyme domains (Lic26A and Cel5E), a family 11 carbohydrate binding module (CBM11), and two C-terminal type I dockerins (2)(3)(4). Lic26A is a glycoside hydrolase (GH) 4 family 26 hydrolase that contains ␤-1,3-1,4-mixed linked endoglucanase activity (4,5).…”
mentioning
confidence: 99%
“…Previous studies of C. thermocellum revealed an interesting cellulosomal celH gene that encodes two functional enzyme domains (Lic26A and Cel5E), a family 11 carbohydrate binding module (CBM11), and two C-terminal type I dockerins (2)(3)(4). Lic26A is a glycoside hydrolase (GH) 4 family 26 hydrolase that contains ␤-1,3-1,4-mixed linked endoglucanase activity (4,5). Cel5E is a bifunctional ␤-1,4-endoglucanase/xylanase that belongs to the GH5 family (6,7), and GH5 is the second largest among the 133 GH families (see the CAZy database) (8).…”
mentioning
confidence: 99%